Investments in worker health and labor productivity: Evidence from Vietnam - Massimo Filippini; Suchita Srinivasan (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
The health and safety of workers are important determinants of their productivity. In manufacturing industries, occupational health and safety (OHS) measures are critical workplace practices for employers to ensure better working conditions for employees, particularly in industries with rampant indoor pollution. This paper studies the impact of investments undertaken by small and medium enterprises in Vietnam in worker health and safety (including in air quality improvements, heat and noise protection as well as in lighting measures) on labor productivity using a production function approach and panel data from 2011-2015. We find that the amount invested by the firm per worker has a significant positive effect on labor productivity. Moreover, our results hold true for both small and large firms, and for firms belonging to different subgroups of industries. Given historically poor working conditions in Vietnam, policy implications relate to the importance of OHS measures and pollution abatement in influencing economic outcomes such as productivity.
Keywords: D83; Q18; Q54; C23; C26; 330; Investments in health; Indoor pollution; Labor productivity; Small and medium enterprises; Vietnam